Lessons from the fastest Brazilian unicorn (INMR - Innovation & Management Review, 2023)
Purpose – The purpose of this paper is to analyze the process of why a Brazilian digital startup companyreached unicorn status the fastest.Design/methodology/approach – After the literature review, the authors conducted the questionnairecontaining 13 questions used in 18 in-depth interviews conducted in the case study. Saturation point combinedwith the independent and in-depth analysis of the researchers is used to achieve internal and external validity.The primary data collected underwent an analytical approach, followed by a resource-based view (RBV). RBVdoes not deal with time. There is a gap in the literature and an opportunity here: to analyze the fastest companyto become a unicorn under the RBV lens.Findings – The case reveals that value can be found in traditional sectors, as is the case of the real estatesector. This is a case of a company in the direct home-buying space.Practical implications – The contribution of this paper is both practical, with the seven lessons, andtheoretical. Resources allocated to a specific context in a specific geographic region shift the attention awayfrom the absolute value of resources to the timing of aggregating them. Thus, the contribution accounting fortime is new to the RBV.Originality/value – The originality lies in the analysis of the dynamics of digital businesses with exponentialgrowth.